Analisis Makna Semantik Dalam Puisi “Aku” Karya Chairil Anwar - Agus Sibagariang; Anggi Rahmawati; Rindy Any Br Tarigan; Vika Maria Sagala; Yuliana Sari (STIKes Ibnu Sina Ajibarang, 2024)
This research introduces an analysis of semantic meaning in the poem